The Use of Video Games on Vocabulary Learning in English as Second Language Context - Erfan Fajar Fadillah; Nasrullah Nasrullah; Abdul Muth'im (Universitas Islam Negeri Palopo, 2026)
Vocabulary acquisition is a fundamental aspect of language learning, and the search for effective strategies to facilitate vocabulary development is ongoing. This study explores the potential of video games as tools for vocabulary acquisition in language learners, considering the impact of individual differences. The systematic literature review methodology is employed to analyze previous studies on the topic. The review highlights the advantages of video games, such as their motivational qualities, cooperative learning environments, and real-world contexts that enhance students' communicative skills. Video games provide a safe virtual environment for learners to experiment, receive immediate feedback, and be rewarded, fostering effective vocabulary learning. The review also reveals that context-embedded approaches, motivation, word frequency, game design, and instructional strategies are significant factors influencing vocabulary acquisition through video games. Additionally, learners' individual differences, including age, gaming experience, and language proficiency, affect the effectiveness of video game-based vocabulary learning. These findings underscore the importance of considering instructional design and learner characteristics when incorporating video games into language education. By integrating video games into vocabulary learning, language classrooms can offer engaging and effective instruction that promotes vocabulary acquisition.